An assessment of the effects of psychological support services on college varsity male rowers - Rushall, B. S. (US Rowing, 1990)
Members of a prominent intercollegiate varsity men's rowing program were instructed to develop and use positive self-talk. In a 6 min ergometer test trial, Ss (N = 8) were directed to use normal test-trial thinking for a one minute interval and the prepared positive thoughts for another minute. These minutes of thought concentration were alternated throughout the trial. Seven Ss performed best in the positive thinking condition for an improvement of 1.17% in distance covered in the segment, while one was marginally worse. Ss were not aware of any performance difference between the two thought conditions. Seven Ss performed best in the positive thinking condition for an improvement of -1.17%, while one was marginally worse. Ss were not aware of any performance difference between the two thought conditions. Implication: Mature rowers are able to improve serious training performances by concentrating on prepared positive thoughts. Normal training thinking does not appear to be conducive to the best quality of training response. Instructing how to think positively is a brief easy task that is embraced by mature varsity rowers.